The Modulation Of Detrusor Contractility By Agents Influencing Ion Channel Activity - Kocmálová M.; Ľupták J.; Barboríková J.; Kazimierová I.; Grendár M.; Šutovský J. (Sciendo, 2018)
Background: This study specified the role of several significant ion channels regulating the metabolism of calcium ions in contraction and relaxation of human detrusor muscle in order to identify possible target for future drugs that are capable of treating diseases resulting from impaired detrusor activity, e.g. overactive bladder. Although this disease can be successfully treated with muscarinic receptor antagonists or β3 agonist, many patients may not be suitable for chronic therapy, especially due to the relatively high side effects of the treatment.